Menyemai Hidup Berkelanjutan: Etika Lingkungan Hidup Pada Gerakan Pemberdayaan Masyarakat Berbasis Eco Fashion - Lisnina; Ismar Hamid (Prodi Sosiologi FISIP ULM, 2023)
The Creative and Smart House Foundation is an institution that runs empowerment programs by producing eco fashion products. This research aims to explain the process of community empowerment based on eco fashion, as well as analyzing its impact from an environmental ethics perspective. This research uses a qualitative approach, with a case study type of research. The data collection techniques used were participant observation, in-depth interviews and documentation. Data were analyzed using the Miles and Hubermann interactive model. The research results show that community empowerment carried out by the Rumah Creative and Pintar Foundation covers the scope of empowerment, empowerment and protection. In terms of approach, it tends to lead to a direct action strategy, characterized by a program of ideas that originate entirely from the Foundation. So what is happening at the Foundation currently is that the target community is consumptive of the programs provided by the foundation. The built community does not show any initiative in certain aspects which are the foundation for the realization of an empowered society. The environmental ethic that is being fostered is ecofeminism. Characterized by empowerment programs that empower socially vulnerable communities, most of whom are women. Trying to review the meanings of human (male) domination of nature and women. So this research sees that the Foundation does not reject human domination. But behind human domination, everything is based on the values ​​of love. Apart from that, the community they support is always careful about production waste, namely not allowing the production waste produced to pollute the earth or have a negative impact on the environment. In this case, the empowerment program is quite capable of changing the perspective of the target community in making life choices.